(3YLGdI GdeHJOF aj GdCfSGHs - (3CHh HcQ Rjf GdOjf eMeO Hf ehSi Hf YKeGf Hf MGRe GdMGRej, GdMGRej,J (B584 (3g` s
(3ChdgG (B:s
(3GdMeO ddg HGQF GdfSe hNGdb GdCfhGQ hGdXde , hehLO GdCTjGA ef GdYOe s
(3BNQgG (B:s
(3EbJUQJ Ydi gPG GdbOQ GdPi CedjJg , djchf egjLkG YRe GdeHJOF ai EOQGc TCh GdefJgi , hGddg GdeYje hHg CSJYjf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B117s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B105 s
(3eUOQ GbJfGA GdCUd (B:s
(3ajV Gddg (B(2125) s
Keywords: (3GdJGQjNs